The Everyday Untamed - Bailey, Skye (WritingThreeSixty, 2024)
Background: A result of the inaugural Karavan Stories Workshop and Anthology Project, Tiger, a ferocious short story anthology, has emerged from the undergrowth. The title of the anthology, which served as the theme from which the authors developed their stories (some more literally than others), was inspired by the case in which a tigress escaped from a private farm in Gauteng, South Africa in early 2023 and remained at large for a number of days until she was cornered and euthanized. Featuring works from eleven South African authors, and ChatGPT, the stories in Tiger explore grief, the unknown and untamed, dysfunctional families and complex characters with often animalistic language that shines a light on the wild side of everyday life -and the reverse.